CONTENT FACTORS AND PRINCIPLES OF PREPARING FUTURE EDUCATORS FOR RESEARCH ACTIVITY - Lola Namazbayeva (European International Journal of Pedagogics, 2023)
In this article, the content, structure, factors and principles of the research activities of future educators are highlighted and the reaction to them is expressed. General and special research develops competences, organizes the student's joint research activity and causes the development of research activity